Cost‐effectiveness of intensification with sodium‐glucose co‐transporter‐2 inhibitors in patients with type 2 diabetes on metformin and sitagliptin vs direct intensification with insulin in the United Kingdom. Issue 4 (20th January 2019) - Pawaskar, Manjiri; Bilir, S. Pinar; Kowal, Stacey; Gonzalez, Claudio; Rajpathak, Swapnil; Davies, Glenn
Abstract : Aim: To evaluate the long‐term cost‐effectiveness of an intensification strategy with sodium‐glucose co‐transporter‐2 (SGLT2) inhibitors (pathway 1) compared with NPH insulin (pathway 2) in patients with type 2 diabetes (T2D) in the United Kingdom who were not at goal on metformin and sitagliptin. Methods: Cost‐effectiveness analysis was performed using the well‐established, validated IQVIA CORE Diabetes Model from the payer perspective over a patient's lifetime. Randomized clinical trials informed treatment effect measures, while public or published sources informed economic inputs. Scenario analyses of glycated haemoglobin (HbA1c), hypoglycaemia rate, body mass index effects, SGLT2 inhibitor cardiovascular protective effects, and population characteristics were conducted to assess the robustness of results. Results: Pathway 1 increased life‐years and quality‐adjusted life‐years (QALYs) compared with pathway 2 (13.49 vs. 13.37, and 9.40 vs. 9.22, respectively). Additional drug costs in pathway 1 were offset by diabetes‐related complication decreases, leading to slightly lower direct medical costs for pathway 1 (£25747 vs £26095). Pathway 1 was therefore cost‐neutral (no interpretable incremental cost‐effectiveness ratio), while improving clinical outcomes. Scenario analyses consistently showed cost‐neutrality or cost‐effectiveness of pathway 1. The highest result remained less than £3000/QALY, reflecting older patients (≥65 years) with lower baseline HbA1c (7%). Conclusions: For UK patients with T2D not at goal on metformin and sitagliptin therapy, treatment intensification with SGLT2 inhibitors prior to NPH insulin is cost‐neutral or cost‐effective compared with immediate NPH insulin intensification.